'How do they want to know?' Doctors' perspectives on making and communicating a diagnosis of dementia. (November 2019) - Bailey, Cate; Dooley, Jemima; McCabe, Rose
Abstract: Recent drives to facilitate earlier identification of dementia have led to increased memory clinic referrals and diagnoses. This study explored the perspectives of memory clinic doctors on making and delivering diagnoses. Four focus groups were conducted with 13 psychiatrists and two geriatricians in the UK. Transcripts were coded line by line using NVIVO. Thematic analysis identified 39 categories, 18 sub-themes and eight overarching themes. Inter-rater reliability on 31% of the data was 0.89. Increased public awareness of dementia was viewed positively in facilitating access to diagnosis and treatment. Doctors viewed diagnosis as a process and expressed concerns about limited pre-diagnostic counselling and post-diagnostic support. In diagnostic delivery doctors sought to develop a narrative drawing on the patient's report of symptoms and adjust explanations to patient preferences and awareness. However, tailoring the delivery to the individual patient was challenging when meeting for the first time. These consultations often involved three participants (doctor, patient and relative), who were felt to have differing needs and expectations. Doctors emphasized that delicacy was required in deciding in what could be discussed in front of both parties, however also stressed the importance of explicitly naming 'dementia'. Efforts were made to balance honesty and hope when discussing prognosis and medication. The work was sometimes emotionally distressing, with limited supervision. Existing communication training was felt to be inadequate for consultations involving triads or people with cognitive impairment. Delivering a dementia diagnosis is a nuanced and challenging task. Negotiating honest descriptions of a life-limiting condition whilst instilling hope is further complicated when cognitive impairment affects comprehension. Misunderstandings at the time of feedback may limit patient opportunities for informed future planning afforded by early diagnosis. Doctors in memory clinics would benefit from evidence based training and supervision to prepare them for these emotionally challenging and complex consultations.